(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
The rapid urbanization and increasing number of motor vehicles have led to significant challenges related to parking management in urban areas. This article explores the various aspects of parking and parking management, including types of parking, design considerations, the impact of parking on traffic congestion, and innovative solutions to parking problems. By analyzing different parking strategies and their effectiveness, the study aims to provide insights into optimizing urban parking infrastructure to enhance mobility and reduce environmental impact.